Partial Least Squares Analysis: E-Marketing Orientation Model To Support Strategic Business Performance In The Weaving Industry In The District And City Of Payakumbuh - Ali Ahmad, Faisal; Iryani, Nelvia; Marafikha Afwa, Hutrisia (Dinasti Publisher, 2024)
Weaving is a fabric-making technique whose raw material is fiber or yarn. Weaving is one of the forms of art that not only has aesthetic, but also has functional value in fulfilling daily needs. This study aims to see the effect of e-marketing orientation on strategic business performance mediated by e-trust in the weaving industry in Lima Puluh Kota Regency and Payakumbuh City. This study uses a quantitative approach, analyzed using the SEM-PLS method with a sample size of 36 people. The results showed that e-marketing orientation has a negative and insignificant influence on strategic business performance. E-marketing orientation has a positive and significant influence on e-trust. E-trust has a positive and significant influence on strategic business performance. E- marketing has a positive and significant influence on strategic business performance through the mediating role of e-trust. The implication of this research is that the potential of e-trust with e- marketing is an effective strategy in improving strategic business performance and achieving success in an increasingly competitive digital environment. So it is necessary to have a good understanding of e-marketing technology by paying attention to e-trust aspects and integrating it into marketing and operational strategies to achieve strategic goals.